2010
DOI: 10.1007/s10067-010-1415-5
|View full text |Cite
|
Sign up to set email alerts
|

Influenza H1N1 infection in a patient with psoriatic arthritis in treatment with Adalimumab: a case report

Abstract: In March 2009 was the beginning of an epidemic flue caused by avian influenza A virus H1N1. The disease varies from mild to serious and fatal cases. There are many hypotheses explaining why this virus infection would be fatal. One of these is the impaired immune response of the infected patient. The use of tumor necrosis factor-alpha inhibitors may cause decreased immune response and greater susceptibility to infections. We presented a case of a patient using adalimumab that have developed H1N1 without complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Considering the absence of hospital admissions and particularly serious symptoms, and the limited number of patients who changed therapy during ILI, the impact of the pandemic can certainly be considered as light among the sample considered by us; the rarity in the literature of reports of the effect of influenza viruses on patients being treated with biotechnological drugs during the pandemic appears in line with this consideration (20,21). Discussion in the literature of proof in laboratory animals of the responsibility of TNF-α as a mediator for pulmonary inflammation during viral pneumonia, and the positive effects it has the treatment with anti-TNF on symptoms and anatomopathological lesions in the same animals seems important (22,23).…”
Section: N Discussionmentioning
confidence: 86%
“…Considering the absence of hospital admissions and particularly serious symptoms, and the limited number of patients who changed therapy during ILI, the impact of the pandemic can certainly be considered as light among the sample considered by us; the rarity in the literature of reports of the effect of influenza viruses on patients being treated with biotechnological drugs during the pandemic appears in line with this consideration (20,21). Discussion in the literature of proof in laboratory animals of the responsibility of TNF-α as a mediator for pulmonary inflammation during viral pneumonia, and the positive effects it has the treatment with anti-TNF on symptoms and anatomopathological lesions in the same animals seems important (22,23).…”
Section: N Discussionmentioning
confidence: 86%
“…In the past, cases of epidemic severe influenza viral infections have been described: Serrato et al reported a case of swine influenza A (H1N1) infection in a psoriatic patient on adalimumab. 2 Furthermore, Kling et al described a patient with psoriasis taking immunosuppressive drugs resulted positive for influenza A (H1N1) who, after an initially efalizumab therapy, was switched to infliximab for a severe psoriatic flare and died after her first infusion. 3 Based on previous cases of death or increased risk of infection from viral diseases in immunosuppressive patients, we would like to stress the importance of a therapeutic reassessment of all psoriatic patients, chronically treated with immunosuppressive drugs, that weaken the immune system and make them more susceptible to opportunistic infections.…”
mentioning
confidence: 99%
“…In particular, anti-influenza activity was reported for benzbromarone, ambraxol and tannic acid [168,169,170]. Kinase inhibitors, such as dinaciclib, flavopiridol, SNS-032, and MK2206, and TNF inhibitors, such as etanercept, adalimumab and infliximab, as well as a lipid-lowering simvastatin and antibacterial vancomycin, rifampicin, and erythromycin, were also reported to possess anti-IAV activity [13,104,107,108,116,128,129,147,166,170]. Interestingly, some of the identified inhibitors could be used for treatment of pain and inflammation associated with severe infections [96] (Patent US 20130123345 A1).…”
Section: Combination Of Various Omics Techniques Identifies Potentmentioning
confidence: 99%